Microglia and Immune cells interactions in multiple sclerosis cognitive impairment: a postmortem study - Catarina Barros; Ainhoa Alberro; Adelaide Fernandes (Journal of Neuroinflammation)
Abstract Multiple Sclerosis (MS), a neuroinflammatory disease of the central nervous system, is one of the commonest causes of non-traumatic disability among young adults. Impaired cognition arises as an impactful symptom affecting more than 50% of the patients and with substantial impact on social, economic, and individual wellbeing. Despite the lack of therapeutic strategies, many efforts have been made to understand the mechanisms behind cognitive impairment in MS patients. Here, we aimed to investigate whether microglia-derived synaptic elimination and immune interactions are exacerbated in MS patients with impaired cognition when compared to non-demented controls (NDC) and cognitively preserved MS patients, that may clarify the role of immune cell interplay in MS cognitive deficits. Postmortem hippocampal samples were obtained from NDCs and MS patients. Sixteen MS patients were categorized based on their cognitive status: preserved cognition (MSCP) and impaired cognition (MSCI). Immunohistochemistry studies were conducted to explore the density of microglia, their role in synaptic engulfment, and their interaction with CD8+ immune cells in the context of cognitive impairment in MS. In high synaptic density hippocampal regions, MSCI patients exhibited a massive presence of microglia cells actively engulfing both excitatory and inhibitory synapses, accompanied by morphological alterations. Additionally, there was an increased expression of the complement protein C1q particularly localized at inhibitory synapses within microglia cells, suggesting a preferential engulfment of complement-tagged inhibitory synapses in MSCI patients. Furthermore, in hippocampal lesions of MSCI patients, we detected a significant infiltration of microglia and CD8 T cells that may be contributing to the smouldering MS and cognitive deterioration. These findings demonstrate that cognitive deficits occurring in MS are associated with microglia engulfment of C1q-tagged inhibitory synapses, which may be driven by direct or indirect stimulation from CD8+ T cells.